2020
DOI: 10.1186/s13041-020-00595-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel Shank2 transcriptional variant in Shank2 knockout mouse model of autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a group of neurodevelopmental disorders that are highly heterogeneous in clinical symptoms as well as etiologies. Mutations in SHANK2 are associated with ASD and accordingly, Shank2 knockout mouse shows ASD-like behavioral phenotypes, including social deficits. Intriguingly, two lines of Shank2 knockout (KO) mouse generated by deleting different exons (exon 6-7 or exon 7) showed distinct cellular phenotypes. Previously, we compared gene expressions between Shank2 KOs lacking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Therefore, the simple suggestion of a hypomorphic SHANK does not explain the highly variable phenotypes in Shank KO mice and patients with SHANK mutations. Other putative SHANK isoforms may still be present and could play additional roles, which may have obscured the detailed functional analysis of SHANK and masked specific phenotypes in Shank KO mouse models [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the simple suggestion of a hypomorphic SHANK does not explain the highly variable phenotypes in Shank KO mice and patients with SHANK mutations. Other putative SHANK isoforms may still be present and could play additional roles, which may have obscured the detailed functional analysis of SHANK and masked specific phenotypes in Shank KO mouse models [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Shank2 mutant mouse models, anxiety-like behavior, hyperactivity, abnormal social behavior and dysregulation of synaptic molecules have been observed in specific regions of the brain [30].…”
Section: Discussionmentioning
confidence: 99%
“…A novel Shank2 transcriptional variant in a Shank2 deficient mouse model of ASD has shown that two lines of Shank2 knockout mice generated by deleting different exons (exon 6-7 or exon 7) showed distinct cellular phenotypes. Lee et al [7] also found expression of a novel exon (exon 4 ′ or e4') between the existing exons 4 and 5 in the Shank2 model of e6-7 Shank2 knockout mice. The results suggested an example of genetic indemnity, leading to phenotypic heterogeneity among ASD patients with the same gene mutation.…”
Section: Shank Family Of Genesmentioning
confidence: 94%
“…Moreover, it has recently been demonstrated that altered expression of specific genes are involved in processes of neurite elongation and synapse formation in the early developmental periods of MAGE Family Member L2 (Magel2)-deficient mice [5], which is another model known for the presence of autismlike symptoms. Currently, it appears that crucial factors that play a role in the pathogenesis of autism are defects and abnormalities found in postsynaptic density proteins [6][7][8]. Alterations for a wide range of postsynaptic density molecules and scaffolding proteins are currently being investigated at the molecular and cellular level in the context of neurodevelopmental disorders, with membrane-associated guanylate kinases representing the largest group amongst them [9].…”
Section: Introductionmentioning
confidence: 99%